Pengaruh Latihan Ladder Drill terhadap Peningkatan Kelincahan pada Futsal Putra Bintang Lima FC Semarang - Filda Dwi Anggraini; Indra Ramadhan (MAN Insan Cendekia Jambi, 2026)
The purpose of this study is to ascertain if ladder workouts help male futsal players from Bintang Lima FC Semarang become more agile. A quasi-experimental study using a one-group pretest-posttest design was the research methodology employed. Thirteen players were chosen by purposive sampling to make up the sample. Three training sessions each week were held over the course of the six-week ladder drill training program. The icky shuffle, reverse icky shuffle, two-foot forward, two-foot sideways, and in-and-out were the movement variants used. The Illinois Agility Test (IAT) was used to gauge agility levels, and the Paired Sample t-Test was used to analyze the results. Agility increased after the training session, according to the study's findings. The average pre-test time of 18.70 seconds decreased to 17.45 seconds in the post-test, a difference of 1.25 seconds. The ladder drill training program implemented showed a significant positive impact on the agility of the men’s futsal players at Bintang Lima FC Semarang. This was confirmed by statistical data, with a calculated t-value of 15.623 far exceeding the critical t-value of 2.179 and supported by a p-value of 0.000, which is still below 0.05.